Teachers and Pedagogical Specialists in Gifted Education - Sharlanova, Valentina (Formazione & insegnamento, 2018)
The article is devoted to an important issue at the beginning of the 21st century – the work with gifted and talented children/ students and the competencies of pedagogical specialists for this work. The design, organization and conduct of gifted education trainings with several target groups of pedagogical specialists and students-future pedagogues are discussed. These trainings are implemented within a European partnership project, two national educational projects and one research university project. Examining the state of the problem of gifted children in Bulgaria is presented. Every training target group was include in a surveys of the need to develop forms of training for teachers and other educational professionals to develop the competences to work with gifted children and students; identifying problems, perspectives, new strategies, teachers profiles in gifted education. Research methods were used such as theoretical analysis of literature on the problem, an analysis of regulatory documents and curricula, interview of people involved in policy, research and practice of work with gifted children. Surveys results are discussed, compared and summarized. Some main problems and perspectives are defined. Conclusions about the coherence between policies, theories and practices are made.